Let $a_i$, $b_i$, etc., be a literal, i.e., a variable or the negation of a variable.

3-SAT concerns formulas in CNF form: $(a_1 \vee a_2 \vee a_3) \wedge \dots \wedge (b_1 \vee b_2 \vee b_3)$ (3-CNF). The problem of whether or not such a formula has an assignment of its Boolean variables such that it evaluates to $1$ is NP-complete.

But if we can convert the 3-CNF formula into a 2-CNF efficiently, then using implication graphs, we know that 2-SAT is in the complexity class P, which would make 3-SAT lives there as well.

So I'm wondering what are the obstacles to doing this?

For example, why can't we do this to remedy it (working with a clause at a time):

$$F := (a \vee b \vee c) \\ u := (a \vee b) \\ \text{But, this assignment (equality) is true} \iff \\ G := (u \vee \bar{a}) \wedge (u \vee \bar{b}) \wedge (\bar{u} \vee a) \wedge (\bar{u} \vee b) =1. \\ \text{ So, } F = 1 \iff \exists u~(u\vee c) \wedge G = 1. $$

And all we've done is swapped out one 3-CNF clause in favor of 5 2-CNF clauses.

I'm not seeing why this wouldn't make 3-SAT polynomial time.

  • 2
    $\begingroup$ While this approach does not work (as explained by John L) to reduce 3-SAT to 2-SAT, something very similar does indeed work to reduce even longer clauses longer down to 3-SAT. This means that 3-SAT is equivalent to general SAT, which allows any size of clause. $\endgroup$
    – Simon
    Aug 17, 2022 at 9:20

1 Answer 1


$u = (a \vee b) \iff (u \vee \bar{a}) \wedge (u \vee \bar{b}) \wedge (\bar{u} \vee a) \wedge (\bar{u} \vee b) =1 $

Unfortunately, the equivalence above does not hold.

Let $a=\text{false}$, $b=\text{true}$, $u=\text{true}$.

  • the LHS is $\text{true}$.
  • the RHS is $\text{false}$ since $\bar u\lor a=\text{false}\lor\text{false}=\text{false}$.

In fact, we can prove the following.
Claim: there is no 2-CNF formula $\varphi(a,b,c,x_1,\cdots,x_m)$ such that $\forall a, b, c\in\{\text{false, true}\}$, $$a\lor b\lor c \iff \exists x_1 \cdots \exists x_m ~\varphi(a,b,c,x_1,\ldots,x_m).$$

  • 4
    $\begingroup$ For the proof of the claim, use the fact that majority on three inputs is a polymorphism of width-2 clauses but not of width-3 clauses. $\endgroup$ Aug 16, 2022 at 20:59

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.